Experimental evaluation of mechanical properties and fracture-fatigue simulation of cryo– and room–temperature–rolled zircaloy–2. (29th December 2014) - Goel, Sunkulp; Gaurav, Kumar; Jayaganthan, R.; Singh, I.V.; Srivastava, D.; Dey, G.K.; Saibaba, N.
In this study, the mechanical properties of mercury–quenched, cryorolled (CR) and room–temperature–rolled (RTR) zircaloy–2 have been examined by performing the tensile and hardness tests. The effect of cryorolling and room temperature rolling on the fracture properties has been evaluated by performing two–dimensional (2D) quasi–static crack growth simulations using finite element approach under plane stress condition. J–integral and internal energy of the mercury–quenched, CR and RTR zircalloy–2 are evaluated and compared with each other. The S–N curves for mercury–quenched, CR and RTR zircaloy–2 are obtained through finite element simulations. After performing the fracture and fatigue simulations, it is found that 85% cryorolled zircaloy–2 possesses better fracture and fatigue behaviour when compared with mercury–quenched and 85% RTR zircaloy–2.